In silico drug design strategies for discovering novel tuberculosis therapeutics - Canales, Christian S. Carnero [UNESP]; Pavan, Aline Renata [UNESP]; dos Santos, Jean Leandro [UNESP]; Pavan, Fernando Rogério [UNESP] (Taylor & Francis, 2024)
Introduction: Tuberculosis remains a significant concern in global public health due to its intricate biology and propensity for developing antibiotic resistance. Discovering new drugs is a protracted and expensive endeavor, often spanning over a decade and incurring costs in the billions. However, computer-aided drug design (CADD) has surfaced as a nimbler and more cost-effective alternative. CADD tools enable us to decipher the interactions between therapeutic targets and novel drugs, making them invaluable in the quest for new tuberculosis treatments. Areas covered: In this review, the authors explore recent advancements in tuberculosis drug discovery enabled by in silico tools. The main objectives of this review article are to highlight emerging drug candidates identified through in silico methods and to provide an update on the therapeutic targets associated with Mycobacterium tuberculosis. Expert opinion: These in silico methods have not only streamlined the drug discovery process but also opened up new horizons for finding novel drug candidates and repositioning existing ones. The continued advancements in these fields hold great promise for more efficient, ethical, and successful drug development in the future.
Keywords: anti-tubercular compounds; computer-aided drug design; drug discovery; ligand-based drug design; molecular docking; structure-based drug design; Tuberculosis